Kejadian khalwat di bandaraya Pulau Pinang (Perbandingan khas dengan Bukit Mertajam) / Abd Halim Abd Hamid - Abd Halim, Abd Hamid (1977)
The proposed research study is somewhat related to the decline in moral sex which is observed to be widespreading and is now covering a very large portion in our country. It is one of the social problems which has been very much discussed. The choice of "khalwat" as the main theme of this research study is due to the serious condition as one type of sexual promiscuity. The Islamic Laws has clearly stated that the religion Islam forbids the action of "khalwat". However, it is yet still widespread although it should be a strong principle of Islam in our country. Therefore, urbanisation is basically the effect of living in which is found characteristics of conflict of norms, rapid social changes, increased mobility of the population, emphasis on material goods and individualism, decline in intimate communication and increased release from formal and informal control. The characteristics, in turn, create a sense of frustration and give rise to situation which is conducive to khalwat, including sexual deviance. When legitimate means of achieving desired social goal is bloced, man will seek other means to reach that goal.